Minority Arab voting: village dynamics and electoral observations in Israel. Issue 1 (2nd January 2018) - Miles, William F.S.
ABSTRACT: For all the novelty of a democratizing "Arab Spring", there have long been pockets in the Middle East where Arabic-speaking voters have gone to the polls in competitive elections, albeit as minority citizens. This article sheds light on such voting at the grassroots level, in Israel, where passions are intense even as the issues and candidates are local. Contradictions between Western notions of electoral democracy and the power of the Arab extended family ( hamula ) result in what we call "electoral hamulism ". Unexamined heretofore in the scholarly literature are the variability of polling station openness and the methodology of electoral observation in the Arab electoral world. Also underappreciated are psycho-cultural consequences of electoral loss. Overall, the article takes up Valbjørn's call for "meta-study" analysis and "self-reflective" rethinking of the study of Arab politics.